A brief review of liquid heat transfer materials used in concentrated solar power systems and thermal energy storage devices of concentrated solar power systems. Issue 2 (18th September 2022) - Wang, Gang; Pang, Shicheng; Jiang, Tieliu
Abstract: Solar power generation is an effective approach to promote the achievement of carbon neutrality. Heat transfer materials (HTMs) are important for concentrated solar power (CSP) systems and their accessary thermal energy storage (TES) devices. The performances of HTMs can influence the operation behaviors of CSP systems and TES devices. On the whole, the HTMs can be divided into three categories according to their physical states, which are the liquid, gaseous, and solid HTMs, respectively. This article presents a brief review of research works on liquid HTMs used in CSP systems and TES devices of CSP systems, mainly including different kinds of molten salts, heat transfer oils, nanofluids, liquid metals, and water. Some typical practical applications, experimental and simulation studies on different kinds of liquid HTMs used in CSP and TES systems are introduced, and the advantages, disadvantages, and further research and development work prospects of different kinds of HTMs are briefly summarized. This article aims to providing a reference for researchers in solar thermal power field. Abstract : This article presents a brief review of research works on liquid heat transfer materials used in concentrated solar power (CSP) systems and thermal energy storage devices of CSP systems, mainly including different kinds of molten salts, heat transfer oils, liquid metals, nanofluids, and water. It aims to providing a reference for researchers in solar thermal power field.